Cue Ball Arthroplasty With Humeroradial Total Elbow Arthroplasty (TEA) Revision: An Approach to Managing Infection and Severe Ulnar Bone Loss in TEA. (September 2020) - Gerow, Daniel E; Tan, Emily H; Bamberger, H Brent
Total elbow arthroplasties (TEA) have become more prevalent as indications expand. However, TEA complications remain a treatment conundrum. One such complication, periprosthetic joint infections (PJIs) have been reported to occur in up to 12% of all TEA procedures. Irrigation and debridement with retention of hardware and antibiotic suppression has a high failure rate. Two stage revisions of TEA, while more morbid, is an effective approach with previous studies showing a 79% eradication rate. These cases are often associated with periprosthetic bone loss, adding to the surgical complexity. In our case report, we present the case of a 59 year old diabetic male with a primary TEA secondary to a distal humerus fracture who developed a deep infection and was successfully treated with explantation, cue ball antibiotic cement arthroplasty, and humeroradial revision. This case report will discuss the cue ball antibiotic spacer technique and humeroradial revision as a salvage procedure in TEA revisions in the setting of extensive ulnar bone loss.